INDEKS PERSEPSI KORUPSI DAN PEMBANGUNAN MANUSIA TERHADAP PERTUMBUHAN EKONOMI DI NEGARA-NEGARA ASIA TENGGARA - Muhammad Fajar; Zul Azhar (Universitas Negeri Padang, 2018)
This research aims to know and analyze determine of corruption and the human development index to economic growth in Southeast Asian countries. This research use panel least square and Fixed Effect Model. The estimation result should that corruption has a possitive and significant effect on economic growth in Southeast Asian countries and the human development Index has a possitive and significant effect on economic growth in Southeast Asian countries. From the result of this research, to increase economic growth, the government in SoutheastAsian countries must strengthen the bureaucratic and legal institutions of a country,increase the role of the government or related agencies in monitoring and crackingdown on corruption that results in lossof government productivity and allocating resources appropriately so that the creation of peace and prosperity among the countries in Southeast Asian. Keywords: Economic Growth, Corruption, Human Development Index